KEDAULATAN ALLAH DALAM KARYA PEMILIHAN OLEH KASIH KARUNIA-NYA: SEBUAH KAJIAN BIBLIKA EFESUS 1:4-6 - Marlin, Jeny; Simanjuntak, Hotman Parulian; Kumowal, Royke Lantupa (DA'AT : Jurnal Teologi Kristen, 2025)
The sovereignty of God is the main principle that underlies all actions and works of God, based on His grace. One tangible form of God's loving sovereignty is His election of humanity to receive salvation through Jesus Christ. The issue many believers face is that they have not fully understood the meaning and implications of election. In fact, awareness of this truth can foster a deep sense of gratitude and recognition of the greatness of God's love and grace in the life of every believer. This research aims to explain that election is not the result of human effort or will, but rather originates from the will of God Himself, who is sovereign and full of grace. The method used is descriptive through literature study and exegetical-based biblical research. A review of various previous studies shows a narrow understanding of God's sovereignty. The novelty of this article lies in the exegetical results of Ephesians 1:4-6, which have not been widely discussed explicitly in current academic literature. The findings indicate that God chose His people even before the world was created. This means that God's decision to save certain individuals has been established since eternity, based solely on grace. In conclusion, understanding this divine election is crucial in Christian faith, as it shows that salvation entirely comes from God, not from human ability or goodness.